The beta-thalassaemia mutations in the population of Cyprus - Baysal, E; Indrák, Karel; Bozkurt, G; Berkalp, A; Aritkan, E; Old, J.M; Ioannou, P; Angastiniotis, Michael; Droushiotou, A; Yuregir, G.T (British journal of haematology, 1992)
We have identified the beta-thalassaemia alleles in nearly all known Turkish Cypriot beta-thalassaemia homozygotes and in over 700 Greek Cypriot beta-thalassaemia heterozygotes living on the island of Cyprus. The data confirmed earlier observations that the IVS-I-100 (G-->A) mutation is present for about 74-80%, while three other alleles [IVS-II-745 (C-->G), IVS-I-6 (T-->C), IVS-I-1 (G-->A)] occur at frequencies of 5-8%. Nearly identical percentages were observed for the two Cypriot groups, quite different from those for beta-thalassaemia patients from Greece and Turkey. This suggests close contacts between the two Cypriot communities during many centuries without a major recent influence from Greek or Turkish beta-thalassaemia carriers.
Keywords: alely; mutace; Thalassemia; Kypr; Alleles; talasemie; lidé; Turecko; Cyprus; Mutation; Řecko; Turkey; Greece; Humans